Synthesis and Dopamine Receptor Binding of Some Pyrazolo[3',4':6,7]azepino[5,4,3-cd]indoles - Gmeiner, Peter; Hübner, Harald; et al. (Heterocycles, 2003)
A synthesis of some substituted pyrazolo[3′,4′:6,7]azepino[5,4,3-cd]indoles is described and their affinities to dopamine receptors were evaluated. The tested compounds (3a-d and 4a,b) showed micromolar affinity to the bovine D1 receptor subtype and the human D2, D3 and D4 receptor isoforms.
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.lphch.synthe